A practical numerical approach for the determination of flow contribution of multi-zones wellbores - Tarom, N.; Hossain, Mofazzal (2017)
Copyright 2017, Society of Petroleum Engineers. In these downturn oil price occasions, the establishment of a numerical model may become a reward in the continually on-screen tracking of the challenging issues such as evaluation of zones flow contribution; investigation of alternative methods in lieu of well interventions and prediction of wellbore temperature profile in the operation of multi-zones producing wellbores. The new approach is based on energy, mass and momentum balance equations. The study briefly describes calculation of overall heat transfer coefficient which is based on the heat resistivity of different layers around a wellbore as well as the heat difference between wellbore and surrounding ground. A simplified numerical model is developed based on the overall heat transfer coefficient which accounts all modes of heat transferring mechanism. The model has been designed to predict wellbore temperature profile along a multi-zones production wellbore. The model explores wellbore temperature profiling both for singlephase and multi-phase production scenarios. The proposed model has been run for the prediction of wellbore temperature profile for a published oil producing well perforated along three different intervals with the contribution of all intervals in the production. Predicted temperature profile is successfully applied for the investigation of flow contribution of each layer considering key thermal characteristics of single- and multi-phase fluid flow along the wellbore. The predicted temperature profile has been compared with the real data; and a good agreement is demonstrated. This is important as it demonstrates that the proposed model can predict wellbore temperature distribution on a real-time basis to continuously monitor downhole temperature without performing well intervention or installing mechanical tools. Also, to explore the impact of flow rate and production string size on the wellbore temperature profile, sensitivity analyses have been carried out. It has been found that both flow rate and production string size may have a significant influence in the prediction of wellbore temperature profile. The major conclusion of sensitivity analysis of this study is that the higher production rates and smaller tubing sizes results a higher wellbore and wellhead temperature, which can be as a consequence of friction effect along the producing string. The novelty of this study is to develop a governing equation as well as to develop a computer simulator for evaluation of wellbore temperature and flow profiles along multi-zones producing wellbores both accurately and quickly. As a result the study may turn aside the necessity of performing well intervention and downhole sensors installation which may significantly reduce well intervention risks and costs.